2019
DOI: 10.1029/2019jg005063
|View full text |Cite
|
Sign up to set email alerts
|

Land Use, Not Stream Order, Controls N2O Concentration and Flux in the Upper Mara River Basin, Kenya

Abstract: Anthropogenic activities have led to increases in nitrous oxide (N2O) emissions from river systems, but there are large uncertainties in estimates due to lack of data in tropical rivers and rapid increase in human activity. We assessed the effects of land use and river size on N2O flux and concentration in 46 stream sites in the Mara River, Kenya, during the transition from the wet (short rains) to dry season, November 2017 to January 2018. Flux estimates were similar to other studies in tropical and temperate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 48 publications
(116 reference statements)
4
19
2
Order By: Relevance
“…On the other hand, this study reports higher N 2 O concentration than a river in New Zealand (114% saturation, Clough et al 2011) and African rivers in general (0.26 μ g‐N L −1 , Borges et al 2015), and higher N 2 O fluxes than a coastal watershed in North Carolina (0.31 mg‐N m −2 d −1 , Stow et al 2005), rivers on the Tibetan Plateau (0.18 mg‐N m −2 d −1 , Qu et al 2017), and boreal rivers (0.05 mg‐N m −2 d −1 , Soued et al 2016). However, our average N 2 O concentration is lower than nearby first‐order streams in Connecticut (0.63 μ atm, Aho and Raymond 2019), forested (1.6 ± 2.1 μ g‐N L −1 ) and agriculture (1.3 ± 1.8 μ g‐N L −1 ) streams in Sweden (Audet et al 2020), and agriculture‐influenced rivers in Kenya (0.51 μ g‐N L −1 , Mwanake et al 2019), Belgium (1406%, Borges et al 2018), and the Upper Mississippi River (250%, Turner et al 2016). In summary, the forested watershed in this study had moderate N 2 O concentration and fluxes compared to global rivers and streams of various land uses and land covers, with values higher than boreal and alpine watersheds but lower than many headwater streams and agriculture‐influenced systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, this study reports higher N 2 O concentration than a river in New Zealand (114% saturation, Clough et al 2011) and African rivers in general (0.26 μ g‐N L −1 , Borges et al 2015), and higher N 2 O fluxes than a coastal watershed in North Carolina (0.31 mg‐N m −2 d −1 , Stow et al 2005), rivers on the Tibetan Plateau (0.18 mg‐N m −2 d −1 , Qu et al 2017), and boreal rivers (0.05 mg‐N m −2 d −1 , Soued et al 2016). However, our average N 2 O concentration is lower than nearby first‐order streams in Connecticut (0.63 μ atm, Aho and Raymond 2019), forested (1.6 ± 2.1 μ g‐N L −1 ) and agriculture (1.3 ± 1.8 μ g‐N L −1 ) streams in Sweden (Audet et al 2020), and agriculture‐influenced rivers in Kenya (0.51 μ g‐N L −1 , Mwanake et al 2019), Belgium (1406%, Borges et al 2018), and the Upper Mississippi River (250%, Turner et al 2016). In summary, the forested watershed in this study had moderate N 2 O concentration and fluxes compared to global rivers and streams of various land uses and land covers, with values higher than boreal and alpine watersheds but lower than many headwater streams and agriculture‐influenced systems.…”
Section: Discussionmentioning
confidence: 99%
“…Spatiotemporal controls on lotic N 2 O dynamics are poorly understood, which limits modeling efforts. Spatially, urban (McMahon and Dennehy 1999; Beaulieu et al 2010; Beaulieu et al 2011) and agriculture (Beaulieu et al 2011; Audet et al 2017; Mwanake et al 2019) landcover types have been associated with high terrestrial nitrogen loading and subsequent high lotic N 2 O emissions. However, a recent study showed that forested rivers have similar N 2 O concentration as agriculture rivers (Audet et al 2020).…”
mentioning
confidence: 99%
“…However, areas under current agricultural production when converted to agroforestry lead to a decrease in runoff while increasing groundwater uptakethis is often because of the choice of tree species sich as Eucalyptus that has a massive water demand (Hubbard et al, 2020). Land use, predominantly deforestation and transition to agriculture, was found to influence nitrous oxide levels in the lower elevations of the Mara River network (Mwanake et al, 2019). The effect of forest cover loss leading to reduced capacity to act as a catchment during heavy rainfall and mediate streamflow was identified as a major disruptor to economic activities to the south-west of Mau (Otuoma et al, 2012).…”
Section: The Early and Middle Holocene: 240-100 CMmentioning
confidence: 99%
“…Recent politicking has led to increased illegal settlement, logging and charcoal burning in the forest as a source of income (Nkako et al, 2005;Were et al, 2013). These increased human population pressures on the forests have further fragmented wildlife populations, with subsequent erosion and water distribution issues having consequences for downstream ecosystems and populations (Gichana et al, 2015;Mwangi et al, 2017;Dutton et al, 2018;Mwanake et al, 2019). Neighbouring Mau forest blocks have undergone varying degrees of anthropogenic modifications impacting vegetation biodiversity, soil geochemistry and topsoil seed bank; however, ecological restoration potential remains (Kinjanjui et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is also anticipated that the GHG emissions will increase soon due to modern land-use changes that the sub-Saharan Africa region has adopted (Popp et al 2010). Although the fluxes are anticipated to be high, there are various uncertainties in the estimates provided due to large insufficient temporal and spatial representation of emissions from agricultural soils (Mwanake et al 2019). In SSA, these changes have significantly impacted the climatic patterns leading to more extended droughts and excessive rainfall that does not support agricultural productivity at the field level.…”
Section: Introductionmentioning
confidence: 99%